Pengaruh Biaya Bahan Baku Dan Biaya Tenaga Kerja Terhadap Volume Produksi : (Studi Kasus Pada Pabrik Tempe Rizqfajaya Periode 2011-2020) - Kena Anjarsari (J-CEKI : Jurnal Cendekia Ilmiah, 2022)
The purpose of this study was to determine and analyze the effect of raw material costs and labor costs on the production volume of the Rizqfajaya Tempe Factory. The research method used in this study is a quantitative method with multiple linear regression analysis tools and the data used are primary and secondary data in the form of financial reports obtained directly from the Rizqfajaya Tempe Factory, the data taken are raw material cost data, labor cost data , and production volume for 10 years. The calculation results show that there is a very strong relationship between the variable costs of raw materials and labor costs on the volume of production. Based on this research, the cost of raw materials and labor costs simultaneously have a significant effect on the volume of production. Partial raw material costs have a significant effect on production volume. Partial labor costs have a significant effect on production volume.